2020
DOI: 10.30954/0974-1712.1.2020.16
|View full text |Cite
|
Sign up to set email alerts
|

Yield Attributes, Yield, Competitive Ability and Economics of Summer Maize-Legume Intercropping System

Abstract: Maize (Zea mays L.), the queen of cereals, is planted with wide spacing and so it offers the scope of intercropping. Considering the benefits of cereal-legume association, an experiment on maizelegume intercropping system was conducted during summer season of 2018 at Bagusala Farm of M. S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The results indicate that mixed planting will improve the efficient use of land and environmental resources if the proportion of B. ischaemum is greater than 50% in the mixtures (Gao et al, 2009;Lithourgidis et al, 2011). Similar studies on legume and non-legume intercropping systems have given RYT values greater than 1, which have been attributed to the differences in the root and shoot characteristics, and the use of different N sources (Lithourgidis et al, 2011;Manasa et al, 2020). Results have shown that the RYT of both species in the mixed planting systems were greatly affected by their mixture ratios than the increasing soil water availability (Table 3 and Figure 4), which indicated that the ratio of the proportion of both species within the replacement series could affect the efficiency of intercropping systems significantly (Aynehband and Behrooz, 2011).…”
Section: Plant-plant Interactions In Response To Varying Mixture Ratiosmentioning
confidence: 62%
“…The results indicate that mixed planting will improve the efficient use of land and environmental resources if the proportion of B. ischaemum is greater than 50% in the mixtures (Gao et al, 2009;Lithourgidis et al, 2011). Similar studies on legume and non-legume intercropping systems have given RYT values greater than 1, which have been attributed to the differences in the root and shoot characteristics, and the use of different N sources (Lithourgidis et al, 2011;Manasa et al, 2020). Results have shown that the RYT of both species in the mixed planting systems were greatly affected by their mixture ratios than the increasing soil water availability (Table 3 and Figure 4), which indicated that the ratio of the proportion of both species within the replacement series could affect the efficiency of intercropping systems significantly (Aynehband and Behrooz, 2011).…”
Section: Plant-plant Interactions In Response To Varying Mixture Ratiosmentioning
confidence: 62%
“…Relative yield total (RYT) values of intercropping were higher than unity in different experiments indicating yield advantage [126]. Moreover, Manasa et al [127] mentioned that MEY was 7.6 t ha −1 when paired row maize was intercropped with groundnut (2:2) as against sole maize yield of 5.7 t ha −1 and RYT was 1.47.…”
Section: Yield Advantagementioning
confidence: 96%
“…The relative yield total (RYT) of the intercropping was higher than in monoculture in the different experiments, indicating a yield advantage. 50 Manasa et al 51 mentioned that MEY was 7,6 t ha − 1 , when maize was intercropped with groundnut (2:2), compared to a maize yield in monoculture, which was 5,7 t ha − 1 , while RYT amounted to 1,47. In our study, the average yield of buckwheat in monoculture was 0,93 t ha − 1 and in intercropping was 0,91 t ha − 1 and the difference was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%